Common mineral nutrients in ankylosing spondylitis: A 2‐sample Mendelian randomization study. (18th July 2022) - Sun, Xiaoya; Deng, Yujie; Ma, Yubo; Shao, Ming; Ni, Man; Zhang, Tao; Wang, Xinqi; Xu, Shanshan; Chen, Yuting; Xu, Shengqian; Pan, Faming
Abstract: Objective: The causal relationship between common mineral nutrients and ankylosing spondylitis (AS) has not been studied. So this Mendelian randomization (MR) study aims to investigate the causal association of varying levels of calcium, zinc, copper, and selenium on AS. Design: We selected 4 elements potentially associated with the onset and development of AS as exposure factors, single nucleotide polymorphisms (SNPs) as instrumental variables, and these SNPs are independent of each other( r 2  < 0.05) and highly correlated with each of the 4 elements ( P  < 5 × 10 −8 ). The 2‐sample MR method takes Inverse‐variance weighted (IVW) and MR‐Egger as the main method and Simple mode (SM), Weighted median (WM 1 ), and Weighted mode (WM 2 ) as supplementary methods to evaluate the causal effect of mineral levels on AS. Results: The IVW analysis does not provide convincing evidence to support a causal association between calcium (odds ratio [OR] = 1.000, 95% CI = 0.994, 1.005, P  = .875), copper (OR = 1.000, 95% CI = 1.000, 1.001, P  = .533) and selenium (OR = 0.999, 95% CI = 0.998, 1.000, P  = .229) and AS. The IVW (OR = 1.001, 95% CI = 1.000, 1.002, P  = .029) and WM 1 (OR = 1.001, 95% CI = 1.000, 1.002, P  = .011) results of zinc show that per standard deviation increment in zinc is a suggestive association with risks of AS, and MR‐Egger (OR = 1.004, 95% CI = 0.996, 1.013, P  = .265) and other supplementary methods indicate that zinc is not causally associated with AS. All MR‐Egger intercept parameters and MR Pleiotropy RESidual Sum and Outlier tests demonstrated the absence of horizontal pleiotropy. Conclusions: This study does not provide convincing evidence to support a causal correlation between calcium, zinc, copper, and selenium with AS.